Diseño Metodológico para determinar el Perfil de Turistas, para Alta Media y Baja Montaña. - Pruna Guanoluisa, Tania Elizabeth (2019)
The purpose of this project is to determine the profile of a tourist in high, medium and low mountain providing basic information of what to do, use and perform in an ascension. For this bibliographical reviews were carried out, as well as interviews with specialized people such as mountain guides belonging to the International Union of Mountain Guide Associations (UIAGM) and to the Ecuadorian Association of Mountain Guides (ASEGUIM) and Sports Medicine Doctor, who know how to handle the subject of mountaineering, hiking and camping. The investigation was developed based on the main problem which was based on the lack of research to determine if a person is fit to perform this sport. For this, it was based on several bibliographical researches that allowed to establish several factors leading to the identification of variables.For the identification of these, explicit information was extracted about the processes of mountaineering practice of several documents and interviews, resulting in the identification of factors such as: psychological, medical, physical and technical, being important topics in the practice of mountaineering. The methodology that was used in the present project is a mixed methodology since the quantitative and qualitative method was used, which intervenes techniques such as field, interview and bibliography. Throughout the research process it was possible to deduce that there are no paradigm models, for the development of an informative test that allows evaluating the physical conditions of the tourist, however it was possible to obtain a test that complies with the most outstanding variables in mountaineering. They are of great importance within this activity, that is, by means of this test the tourists will be able to self-evaluate and know what conditions they are in and verify if they are suitable or not to make an ascent.Finally, all the information collected was established in a procedures manual that will be used for the application of the previously established test.